PERLINDUNGAN HUKUM TERHADAP PARA PIHAK DALAM TRANSAKSI JUAL BELI PAKAIAN JUAL BELI PAKAIAN MELALUI MEDIA INTERNET - RENY ELISA LUMBAN GAOL (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Saidin2. T. Keizerina Devi A3. Mahmul Siregar The form of online clothing purchase agreement protected by ITE (Law on Electronic Transaction) Act in Indonesia is not specifically regulated in legislation in Indonesia, but it does not make a legal vacuum. With a special regulation governing this virtual agreement, it automatically agreements on the internet are subject to ITE legislation. Regarding electronic trading transactions, inseparable from conventional concepts of agreements as contained in those articles essentially describes the engagement of parties on the basis of the needs of each party to derive the achievement of the agreement. The contract on buying and selling clothes by online which is legally protected by ITE is an agreement in the form of electronic. Electronic document in UUTE is meant as electronic information which is made, forwarded, sent, received, or kept in an analogue which can be seen and displayed through computer or electronic system.Keywords: Legal Protection, Stakeholders, Buying and Selling Transaction, Through Internet Media